Mistica: A Marxist Praxis - Gyanwali, Gokarna Prasad (Patan Pragya, 2021)
The Mística is the symbolic or dramatic social movement of Marxism initiated by Brazilian Landless Rural Workers. It is the popular movement practiced by the Communist parties and socialist organizations of the world. It was developed from Latin American liberation doctrine and interpreted as love for a cause, solidarity experienced in collectivity, symbolic presentation of the socialist movement, and belief in radical change. It is one type of philosophical movement which has a demonstrative attachment, praxis of pedagogy, behavioral collectivity, and cultural movement to change the social world guided by the theory of Karl Marx. It has political roots against the homogenization of culture, imperialism, and capitalist domination of the world. It uses art, music, drama, activity, symbol, media, and other modern tools which help the people for emancipation. This article will demonstrate some of the major aspects of mistica based upon the field observation of Brazil and Nepal.